2020
DOI: 10.1116/6.0000273
|View full text |Cite
|
Sign up to set email alerts
|

Lab-based operando x-ray photoelectron spectroscopy for probing low-volatile liquids and their interfaces across a variety of electrosystems

Abstract: The understanding of fundamental processes in liquids and at the liquid/electrode interfaces of electrochemical systems is crucial for the development of new devices and technologies with higher efficiency and improved performance. However, it is generally difficult to isolate and study the component of interest in such complex systems. Additionally, ex situ analyses do not always reflect the same properties under operating conditions. Hence, operando characterization tools are required for observing related e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 85 publications
1
4
0
Order By: Relevance
“…That experimental setup enabled the formation of a liquid film thin enough to probe the IL/electrode interface such that the authors were able to follow the EDL processes by tracing the shifts in the core-level binding energies under bias. While the application of direct current (DC) bias during XPS data acquisition provides steady-state information, demonstrated by us and others as well, our group has previously shown that alternating current (AC) excitation is indispensable for investigation of the dynamics of electrical potential developments. Use of scanning electron microscopy (SEM) for detecting similar changes due to potential induced intensity modulations was also recently reported by us . Both our XPS and SEM investigations revealed that the effects of time-resolved polarization of the metal electrodes can be followed locally up to extremely long-distance (centimeters) and long-time (hundreds of seconds) ranges, in a chemically specific fashion.…”
Section: Introductionsupporting
confidence: 58%
“…That experimental setup enabled the formation of a liquid film thin enough to probe the IL/electrode interface such that the authors were able to follow the EDL processes by tracing the shifts in the core-level binding energies under bias. While the application of direct current (DC) bias during XPS data acquisition provides steady-state information, demonstrated by us and others as well, our group has previously shown that alternating current (AC) excitation is indispensable for investigation of the dynamics of electrical potential developments. Use of scanning electron microscopy (SEM) for detecting similar changes due to potential induced intensity modulations was also recently reported by us . Both our XPS and SEM investigations revealed that the effects of time-resolved polarization of the metal electrodes can be followed locally up to extremely long-distance (centimeters) and long-time (hundreds of seconds) ranges, in a chemically specific fashion.…”
Section: Introductionsupporting
confidence: 58%
“…This experimental setup allowed the formation of a liquid film thin enough to probe the IL/electrode interface, so that the authors were able to follow the EDL processes by tracing the shifts in binding energy under an external potential . While applying such DC potential during XPS data acquisition provides vital steady-state information, our group has previously shown that AC excitation is helpful for understanding the dynamics of electrical potential developments. …”
Section: Introductionmentioning
confidence: 99%
“…Facilitated by their high vacuum compatibility, over the past decade ILs have been fairly well characterized in‐vacuo by X‐ray photoelectron spectroscopy (XPS) as a function of electrochemical potential [34–58] . XPS allows for the determination of surface composition of an IL while also probing the binding energy shifts in the ions ( U XPS ; units of eV) as a function of an external electrochemical potential ( U ; units of V).…”
Section: Introductionmentioning
confidence: 99%